Stress levels and eating behavior among university students in Jordan: A cross-sectional study - Anfal AL-Dalaeen; Nour Batarseh; Zaher Al-Bashabsheh; Baha'Ghandi ALjeradat; Dima Batarseh; Arab Karablieh (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Increased body weight is common among university students; transitioning from high school to university may increase perceived stress levels, thus changing dietary habits and metabolism to promote overweight or obesity. The current study investigates the association between stress and dietary habits among university students in Jordan. MATERIALS AND METHODS: A cross-sectional study was conducted among 221 university students aged between 20 and 25 at Applied Science Private University [ASU]. A self-reported questionnaire was distributed to university students. The questionnaires were divided into three sections: the first was about general characteristics, body weight, change in body weight, and stress eating. RESULT: The survey of 208 participants showed that 64.3% were females, and 84.2% of students lived with their families. Results showed that more than half [51.1%] of the respondents were dissatisfied with their eating habits. Females [57.7%] monitored their food intake more than males did. However, most males [77.2%] reported less eating during stress compared to females. In addition, the data analysis revealed that those who ate more were less likely to monitor their food intake [χ2 =9.734, df = 1, P = .002] or quantity [χ2 =16.704, df = 1, P < .001]. Only 20.8% of the participants preferred sports or hobbies as a stress reduction activity; 29.4% took showers, while 51.1% ignored what made them stressed. Finally, 56.3% of participants reported increased weight after starting university, and it was significantly correlated with stress eating while studying for exams [χ2 =8.762, df = 2, P = .013]. Stress affects university students and can lead to unhealthy eating habits and health issues like obesity. CONCLUSION: Many students face stress during their academic years, which affects their dietary choices. Policies promoting healthy eating habits and stress-reducing activities are important for university students.